Spectral attenuation curves of photon-counting detector CT scans for the differentiation between mucinous and non-mucinous cyst fluids of pancreatic lesions: a proof-of-concept study - Dudás, Ibolyka; Lovász, Borbála; Benke, Márton; Kiss, Máté; Juergens, Markus; Szücs, Ákos; Kaposi, Pál N.; Szijártó, Attila; Maurovich-Horvat, Pál; Budai, Bettina Katalin (BMC medical imaging, 2025)
Abstract - - Background - Spectral imaging via photon-counting detector CT (PCD-CT) scanners allows the generation of spectral attenuation curves. Our study aimed to test the feasibility of spectral attenuation curve analysis for differentiating mucinous from non-mucinous cyst fluids of pancreatic cystic lesions (PCL). - - - Methods - - Our study included 74 patients with PCLs. The classic morphological features were evaluated by an expert radiologist. The spectral attenuation curves were generated from the pancreatic-phase scans. The average CT values were measured on the 70 keV (HU - 70keV - ) and 40 keV (HU - 40keV - ) virtual monoenergetic images (VMIs), and the differences were calculated (HU - Δ40−70keV - ). The cases were divided into training (53 mucinous vs. 19 non-mucinous PCLs) and test (10 mucinous vs. 10 non-mucinous PCLs) datasets. The receiver operating characteristic (ROC) curve analysis assessed the discrimination performance. The intra- and interobserver reproducibilities were evaluated by the intraclass correlation coefficient (ICC). - - - - Results - - On 70 keV VMIs, no significant differences were found between the average CT values of mucinous and non-mucinous PCLs, however, the difference was significant in HU - Δ40−70keV - values ( - p -  < 0.0001). The diagnostic performance of HU - Δ40−70keV - in differentiating between mucinous vs. non-mucinous PCL had AUCs of 0.92 and 0.92 on the training and test datasets, respectively, with a good interobserver (ICC = 0.82) and excellent intraobserver reproducibility (ICC = 0.94). The conventional clinical-radiological model achieved AUCs of 0.85 and 0.86, and with the addition of HU - Δ40−70keV - values its performance increased significantly to 0.98 and 0.94 on the training and test datasets, respectively. - - - - Conclusions - Spectral attenuation curve assessment of cyst fluids could be a useful additional measurement to facilitate the noninvasive differential diagnosis of PCLs.
Gesehen am 01.12.2025